THE INFLUENCE OF ORGANIZATIONAL COMMITMENT, WORK MOTIVATION, AND COMPENSATION ON EMPLOYEE PERFORMANCE AND EMPLOYEE SATISFACTION - Ahmad Muktamar; Jenita Jenita; Musran Munizu; Ambar Kusuma Astuti; Alfa Santoso Budiwidjojo Putra (JURNAL ILMIAH EDUNOMIKA, 2024)
Strong organizational commitment in employees, high work motivation, and compensation are some of the things that a company can pay attention to so that employees can achieve maximum performance and maximum job satisfaction and in the end this will have good implications for the company. This research is quantitative research with an exploratory approach. The data used in this research is primary data distributed to 300 employees of Pt. Sinar Mas Agro is spread throughout Indonesia with a minimum criteria of having worked for one year. The data used is analyzed by Smart PLS 4.0. The research results show that all the independent variables used have a positive relationship and have a significant influence on the dependent variable. Keywords : Organizational Commitment, Work Motivation, Compensation, Employee Peformance, Employee Satisfication.